A further note on the identity of Barbus mussullah Sykes (Teleostei: Cyprinidae) - Knight, J. D. Marcus; Rai, Ashwin; D’souza, Ronald K. P. (Zootaxa, 2014)
Knight et al. (2013a) clarified the identity of Barbus mussullah Sykes, the type species of Hypselobarbus Bleeker, showing it to represent a lineage clearly distinct from Tor Gray (type species Tor hamiltonii Gray (= Cyprinus tor Hamilton)). They showed the two species to be distinguished by a suite of characters, with Hypselobarbus lacking the distinctive median fleshy lobe of the lower lip (present in T. tor), having the last simple ray of the dorsal fin weak (vs. strong, 'osseous'), gill rakers long and branched (vs. short and simple, unbranched) on first gill arch, and the proximal end of the fifth ceratobranchial hooked (vs. only slightly curved). Nevertheless, some subsequent authors (e.g., Ambili et al. 2014; Khare et al. 2014) have persisted in referring Barbus mussullah to Tor, in effect synonymyzing Hypselobarbus (in which 12 species are currently recognized) with Tor and thereby causing confusion with regard to the identities of these groups of fishes which, being large and relatively common cyprinids, are of significant economic importance.